Tunable Spin Correlated‐Plasmons Ranging from Infrared to Ultraviolet in Pr0.6Sr0.4Co1−xMnxO3. Issue 2 (22nd December 2020) - Chaudhuri, Anindita; Chanda, Amit; Chi, Xiao; Yu, Xiaojiang; Diao, Caozheng; Breese, Mark B. H.; Mahendiran, Ramanathan; Rusydi, Andrivo
Abstract : Herein, new spin correlated‐plasmons in Pr0.6 Sr0.4 Co1− x Mn x O3 ( x = 0–0.4) that are tunable and stable at room temperature are demonstrated. Using advanced spectroscopic techniques, the charge, spin, and orbital interaction that triggers the spin correlated‐plasmons in spin‐polarized Co 4+, O 2−, and Mn 4+ is identified. As a function of x, Co 4+ systematically changes the spin state of the spin correlated‐plasmons (from high, intermediate, to low spin), which also sequentially transforms the metallic cobaltite into a Mott insulator. Spin correlated‐plasmons in the IR range, being excited from Co 4+, tend to dominate in the metallic phase of the cobaltites, whereas Mn 4+ and O 2− are the primary source for the spin correlated‐plasmons in the UV–vis ranges in the insulating phase. Abstract : Tunable and stable spin correlated‐plasmons are observed in the UV to IR energy range by optically exciting bulk Pr0.6 Sr0.6 Co1– x Mn x O3 at room temperature. The plasmons are manifested by the systematic transitions of Co 4+ spin state from high spin (HS) to low spin (LS) accompanied by metal‐to‐insulator (MIT) transition of the perovskite cobaltite without changing the crystal structure.